Association of statin pre-treatment with baseline stroke severity and outcome in patients with acute ischemic stroke and received reperfusion treatment: An observational study. Issue 2 (February 2023) - Escudero-Martínez, Irene; Matusevicius, Marius; Pavia-Nunes, Ana; Sevcik, Petr; Nevsimalova, Miroslava; Rand, Viiu-Marika; Kõrv, Janika; Cappellari, Manuel; Mikulik, Robert; Toni, Danilo; Ahmed, Niaz
Background: Statins have an important role in stroke prevention, especially in high-risk populations and may also affect the initial stroke severity and outcomes in patients taking them before an ischemic stroke. Aims: Our aim was to evaluate the association of statin pre-treatment with the severity in acute ischemic stroke (AIS). Methods: We analyzed AIS patients received intravenous thrombolysis (IVT) and/or endovascular thrombectomy (EVT) and recorded in the SITS International Thrombolysis and Thrombectomy Registry from 2011 to 2017. We identified patients with statin information at baseline. The primary outcome was baseline National Institutes of Health Stroke Scale (NIHSS) score. Secondary outcomes were NIHSS score at 24 h, symptomatic intracerebral hemorrhage (SICH) and functional outcome at 90 days after acute intervention. Multivariable linear and logistic regression and propensity score matching (PSM) was used to quantify the effect of statin pre-treatment. Results: Of 93, 849 patients, 23, 651 (25.2%) were treated with statins prior the AIS. Statin pre-treatment group was older and had higher comorbidity. Median NIHSS at baseline was similar between groups. In the adjusted and PSM analysis, statin pre-treatment was inversely associated with baseline NIHSS (odds ratio (OR) = 0.77, 95% confidence interval (CI) = 0.6–0.99 and OR for PSM 0.73, 95% CI = 0.54–0.99, p = 0.004) and independently associated with mild stroke defined as NIHSS ⩽8 in adjusted and PSM analysis (OR = 1.21, 95% CI = 1.1–1.34, p < 0.001 and OR for PSM 1.17, 95% CI = 1.05–1.31, p = 0.007). Regarding secondary outcomes, there were no differences in functional outcomes, death nor SICH rates between groups. Conclusion: Prior treatment with statins was associated with lower NIHSS at baseline. However, this association did not translate into any difference regarding functional outcome at 90 days. No association was found regarding SICH. These findings indicate the need of further studies to assess the effect on statin pre-treatment on initial stroke severity.